Genetics of infectious disease resistance. - Hill, A (1996)
The identification of large numbers of candidates genes and the introduction of methodologies for whole-genome screening have provided new opportunities for elucidating the molecular basis of variable susceptibility to major infectious diseases. 12 genes have been implicated in variable susceptibility to malaria and susceptibility/resistance genes for several other infectious diseases are beginning to be identified. Recent work suggests that large-scale family linkage and population association studies will be a more successful route to human disease genes than extrapolation from mouse models of infection.